THE STYLE USED BY STUDENTS IN LEARNING VOCABULARY - Yuliatin, Fithria Ulfani (Journal of Languages and Language Teaching, 2016)
The purpose of this study is to describe the application of Learning Styles in the vocabulary used by students of SMAN 1 Sakra Timur. To know the percentage of student learning style in vocabulary. Students of grade 2 IPA 1 are less in applied learning styles, students are more sitting and silent, whether they understand what is described or not. In keeping the results of research, conducted data collection using qualitative descriptive. Data obtained from the results of vocabulary and questionnaire tests. On the other hand, the qualitative data comes from student observations as well. Then the data can be seen that students have problems with the vocabulary, from 37 students who are able to achieve it consists of 15 students (40%) able to achieve the Minimum Mastery Criteria with qualifications consisting of 5 students (14%) to Prima, 9 students (24% to Very good, and 10 students (27%) became good, while there were 13 students (35%) who were unable to achieve minimum mastery with poor or failing qualifications. For percentage of learning style preferred by students to learn to use visual learning style, (89%) SS, 3 (8%) S, 1 (2%) TT and nobody chose disagree and strongly disagree. In addition, from the observation, Students are less active to respond to lessons taught due to lack of force learning applied by the teacher.